Contributions of ANPEd to the consolidation process of Brazilian Postgraduate studies: historical paths and current scenarios (Práxis Educativa, 2015)
This article results the bibliographic and documentary search whose the purpose is reconstitute the historicity to search association, in the context of 50 years to the politic institutionalization on Postgraduate in Brazil, with specific emphasis in the ANPEd - National Association of Postgraduate Studies and Research in Education. The analysis was performed based in the recent politics diary association, especially in the monitoring and positioning in the approval of Law 13.005/2014, which deals with the National Education Plan 2014-2024, with reference to Gramsci’s conception of Expanded State. Studies indicate tensions and challenges faced by ANPEd, from the participation of its members in political society, where the formulators change to executors of national policies, while showing the potential and limits of the association to remain as an entity autonomous civil society in defense of a public, free, secular and quality education for all. Keywords: ANPEd. Extended State. National Education Plan.